Adult‐specific insulin‐producing neurons in Drosophila melanogaster. Issue 8 (26th February 2018) - Ohhara, Yuya; Kobayashi, Satoru; Yamakawa‐Kobayashi, Kimiko; Yamanaka, Naoki
Abstract: Holometabolous insects undergo metamorphosis to reorganize their behavioral and morphological features into adult‐specific ones. In the central nervous system (CNS), some larval neurons undergo programmed cell death, whereas others go through remodeling of axonal and dendritic arbors to support functions of re‐established adult organs. Although there are multiple neuropeptides that have stage‐specific roles in holometabolous insects, the reorganization pattern of the entire neuropeptidergic system through metamorphosis still remains largely unclear. In this study, we conducted a mapping and lineage tracing of peptidergic neurons in the larval and adult CNS by using Drosophila genetic tools. We found that Diuretic hormone 44‐producing median neurosecretory cells start expressing Insulin‐like peptide 2 in the pharate adult stage. This neuronal cluster projects to the corpora cardiaca and dorsal vessel in both larval and adult stages, and also innervates an adult‐specific structure in the digestive tract, the crop. We propose that the adult‐specific insulin‐producing cells may regulate functions of the digestive system in a stage‐specific manner. Our study provides a neuroanatomical basis for understanding remodeling of the neuropeptidergic system during insect development and evolution. Abstract : In the fruit fly Drosophila melanogaster, Diuretic hormone 44‐producing neurons start expressing Insulin‐like peptide 2 in the pharate adult stage. This neuronal cluster projects to the crop, an adult‐specific structure in the digestive tract.